MEASUREMENT OF STUDENTS’ MOTIVATION FOR LEARNING A FOREIGN LANGUAGE - K. Katsarova (Trakia Journal of Sciences)
This article measures various subjective and objective indicators of motivation for learning a foreign language among students of Trakia University. The main goal is to derive the overall and instrumental motivation that would affect the respondents, the most pressing needs for learning a foreign language, as well as the flows or the degree of involvement of the respondents. The applied methodology consists of designed surveys, and some of the identified motives would determine the practical application of adequate incentives to maintain the motivation of students for learning a foreign language. The identified factor dependences generally indicate approximately the same intensity in the motives of the respondents, as the high interest in it is explained first of all by the desire of students to gain knowledge of language, but not least of culture, behavior and traditions. The highest degree of motivation is expressed in the desire for their knowledge and skills to find practical realization in different professional environments.